Construction and Preliminary Application of the Carbon-based Spatial Governance Performance Evaluation System ——Taking Zhejiang Province as an Example - Qu, Lin; Xia, Ganlin; Bao, Cunkuan, Prof. (CSID Journal of Infrastructure Development, 2023)
Carbon is generated through human socio-economic activities, with territorial space serving as the medium for these activities. Variations in spatial governance result in differences in the scale, intensity and efficiency of social and economic activities, as well as energy and resource consumption and carbon emissions across diverse functional spaces. Consequently, spatial governance performance should be evaluated using carbon-related indicators. This study initially established a theoretical model for assessing spatial governance performance based on carbon and an evaluation method encompassing three dimensions or indices "level-progress-gap". Zhejiang Province and its 11 prefecture-level cities were selected as the research area for preliminary application to explore the spatial governance performance and existing challenges under differentiated management and control. Finally, policy recommendations were proposed to foster the enhancement of spatial governance performance and the integration of low-carbon development.